Opportunity Cost Analysis and Fiscal Accountability of Indonesia's Board of Peace Membership Commitment 2026: A Public Finance and State Budget Management Perspective - Briyan Nanda Ivansyach; Aqiilah Abiyyi Rafli; Tumija Tumija (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study analyzes the Indonesian government’s financial commitment of US$1 billion (approximately IDR 16.76 trillion) to secure permanent membership in the Board of Peace (BoP), formalized on January 22, 2026. The analysis applies a public expenditure framework integrating opportunity cost, value-for-money, and fiscal accountability to evaluate three key aspects: the trade-offs within the 2026 State Budget, compliance with national financial regulations, and potential risks to fiscal stability. The findings highlight three critical issues. First, the allocation represents a significant opportunity cost, as the amount is equivalent to around 5% of the Free Nutritious Meals program and nearly 7% of the national health budget. It could alternatively fund the annual salaries of approximately 300,000 contract teachers, indicating substantial foregone social benefits. Second, the financing approach of reallocating the Ministry of Defense budget without formal approval through a revised State Budget raises concerns about compliance with the principle of budget specificity, as mandated by Law No. 17 of 2003. This suggests a potential misalignment with established fiscal governance standards and legislative oversight mechanisms. Third, the commitment introduces additional fiscal pressure outside the approved budget structure, which may constrain fiscal space amid ongoing expenditure efficiency policies in 2025–2026. This condition increases the risk of undermining the deficit target of 2.68% of GDP. Overall, this study contributes to public finance discourse by demonstrating how international financial commitments can influence domestic fiscal discipline, accountability, and sustainability in emerging economies.